Other Dimensions of Tax Billing with Gjzeling (Study on Tax Confiscation Officials at KPP Pratama Surabaya Wonocolo) - Dewi Prastiwi; Diana Amalia Puspitasari (Journal of Economics, Business, and Accountancy Ventura, 2017)
Hostage or Gjzeling is one of the tax collection efforts to tax payers in certain places within a maximum period of 6 months from the tax insurer placed in the hostage-taking and this can be extended for about 6 months. Many of the constraints faced by tx confiscation officals are related to the duty of gijzeling. This study aims to explore the ways of gijzeling using a qualitative approach or non-positivistic with interpretive paradigm in approaching the true reality. The result shows that the efforts made for the success of tax confiscation officials in gizjeling process are to: 1) believe that the process of gijzeling is for the law enforcement efforts, the process of education to taxpayers, as well as carrying out the mandate of the State to save the state money; 2) manage the conflict with tax insurer based on the hang rule to the taxpayer, neutral, professional, and uphold integrity; 3) uploading awareness by downloading "brainwashing" penangung pajak